The Effectiveness of Training Problem-Solving Skills on Depression and Anxiety in Mothers of Children with Mental Retardation - رضوان پناهی; احمد غضنفری; طیبه شریفی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: The presence of a mentally retarded child in each family affects the structure and mental health of that family, especially the parents. The aim of this study was to evaluate the effectiveness of training problem-solving skills on depression and anxiety in mothers of children with mental retardation. Methods and Materials: This was a quasi-experimental study with pretest, posttest, and follow-up method along with the control group. The study population was mothers of children with mental retardation in Shahrekord City, Iran, in the year 2016. 30 mothers were randomly selected and assigned to two equal groups of experimental and control. The research instruments were as Beck Depression Inventory second edition (BDI-II) and Beck Anxiety Inventory (BAI). First, both groups were given pretest; then, experimental group was trained for 7 sessions of 2 hours twice a week according to training problem-solving skills; and after training, posttest was taken from both groups. Data were analyzed using covariance method. Findings: Compared with the control group, problem-solving skills reduced depression and anxiety among experimental group (P < 0.050). Problem-solving skills reduced depression and anxiety in mothers of children with mental retardation with covariance changes of 71.9 and 72.7 percent, respectively. Conclusions: Training problem-solving skill can be used as an effective educational program to decrease depression and anxiety in mothers of children with mental retardation.